SISTEM INFORMASI LABORATORIUM KALIBRASI MIGAS (Studi Kasus: Pusat Pengembangan Sumber Daya Manusia Minyak Dan Gas Bumi Cepu) - Joko Handoyo (SIMETRIS, 2015)
As an institution engaged in calibration services at the Center for Oil and Gas Human Resource Development Cepu, the Oil and Gas CalibrationLaboratory needs to continually make breakthroughs or steps so as to improve service to customers. A faster service time and an accountableand credible system are some prerequisites for improving service. In the improvement of calibration services at the Oil and Gas CalibrationLaboratory with the emphasis on information systems, a relatively fast, precise and accurate system is needed. To avoid inefficiency,inefficiency and to improve performance in serving the applicants, it is necessary to design the information system of Oil and Gas CalibrationLab. By using the approach through several stages to analyze and design the system, the process is developed through the use of a cycle ofactivity analyzer and user in a specific (structured), the method SDLC (System Development Life Cycle) with waterfall model. In this systemfor making program online using PHP and MySQL programming language by using CodeIgniter. This information system consists ofcomponents applying for calibration, data input process until calibration certificate information. So that this information system can assist inthe process of calibration service and make agenda report receipt of goods quickly, accurately and easily.